Sugar & Spice Desserts : strategic position defensibility - Allon, Gad; Kahn, Stephanie; Skeba, Mark ([London] : SAGE, 2016)
Sugar and Spice and Sparkles are two companies in the high-end cupcake market that have chosen two different competitive and operating strategies. Sugar and Spice has configured its operations to emphasize a high level of customization. Sparkles has a strategy that emphasizes a narrower range of products. Based on data collected by Sugar and Spice, the question is whether its position is at risk. The case focuses on Sugar and Spice and the defensibility of its position using its current operating system.
Originally Published in: Allon, G., Kahn, S., & Skeba, M. (2012). Sugar & Spice Desserts: Strategic Position Defensibility (case & teaching notes revised 19/04/2012). 5-411-753. Evanston, IL.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: elektronické knihy; electronic books; Sugar & Spice Desserts (Firm); Value analysis (Cost control) -- Case studies; Cost accounting -- Case studies; Competition -- Case studies